2005
DOI: 10.1109/jlt.2005.852023
|View full text |Cite
|
Sign up to set email alerts
|

Noise suppression of incoherent light using a gain-saturated SOA: implications for spectrum-sliced WDM systems

Abstract: Abstract-In this paper, we present an experimental and numerical study of semiconductor optical amplifier (SOA)-based noise suppression and its relevance to high-channel-density spectrumsliced wavelength-division-multiplexed systems. We show that the improvement in signal quality is accompanied by spectral distortion, which renders it susceptible to deterioration in the presence of subsequent optical filtering. This phenomenon originates from the loss of intensity correlation between spectral components of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(61 citation statements)
references
References 27 publications
4
56
0
1
Order By: Relevance
“…Despite the benefits listed above, in the course of our research, we found that the superior signal quality offered by the saturated SOA was noticeably degraded by subsequent optical filtering, leading to a tangential investigation into these effects [13]. Spectral filtering at the receiver is an unavoidable part of SAC and thus places severe limits on the partnership of the two technologies.…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…Despite the benefits listed above, in the course of our research, we found that the superior signal quality offered by the saturated SOA was noticeably degraded by subsequent optical filtering, leading to a tangential investigation into these effects [13]. Spectral filtering at the receiver is an unavoidable part of SAC and thus places severe limits on the partnership of the two technologies.…”
Section: Introductionmentioning
confidence: 73%
“…The gain compression that occurs in saturation acts across the entire gain bandwidth of the SOA and introduces correlations between the intensity noise of the various spectral components propagating through the amplifier. We have shown both experimentally and via simulations [13] that in distinct contrast to thermal light (e.g., the SOA-input light), anticorrelations exist between the intensity noise of different spectral components, which in turn yield reduced fluctuations in the total output intensity (i.e., noise suppression). Subsequent optical filtering removes frequency components that contribute to the intensity smoothing, thereby counteracting the noise suppression introduced by the saturated SOA.…”
Section: B Results and Discussionmentioning
confidence: 96%
See 3 more Smart Citations